MODELING of COST of MACHINES And EQUIPMENT ON THE BASIS OF the BASIC RULES of the RELIABILITY THEORY - O.R. KIRISHIEV (Advanced Engineering Research)
The cost of second-hand machines and equipment may be described by mathematical models of exhibitor function of probability of non-failure operating, which are received with use of the current information of the second-hand machines market.